Effect of Diet on Tissue Levels of Palmitoylethanolamide - S. Hansen, Harald (CNS & Neurological Disorders - Drug Targets, 2013)
Palmitoylethanolamide (PEA) as well as the other N-acylethanolamines (NAEs), e.g. anandamide, oleoylethanolamide, stearoylethanolamide and linoleoylethanolamide, appear to exist in every mammalian cell at low levels, e.g. a few hundred pmol/g tissue for PEA. Their formation can be stimulated by cellular injury and inflammation. In the brain PEA and other NAEs may have neuroprotective functions. PEA levels in tissues seem hardly to be influenced by variation in intake of dietary fatty acids, except in the small intestine where dietary fat results in decreased levels of PEA and other NAEs. In rat small intestine, PEA, oleoylethanolamide and linoleoylethanolamide have anorectic properties. Of other dietary components, only ethanol is known to influence tissue levels of PEA. Thus, an acute intoxicating dose of ethanol will decrease PEA levels in various areas in the brain of rats. The mechanism behind this effect is not known.
Keywords: human